Recent Trends and Prospects of Microbial Fuel Cell Technology for Energy Positive Wastewater Treatment Plants Treating Organic Waste Resources - Sunghoon Son (Korean Society of Environmental Engineers, 2021)
Microbial fuel cell (MFC) technology is receiving a lot of attention recently as a promising technology for generating electricity by treating organic waste resources. Over the past 20 years, the MFC technology has made rapid progress: various research on system architectures, electrochemistry, materials, and microbiology has been conducted for developing practical ideas and fundamental principles. Recently, a lot of research on scaled-up systems for practical application is being conducted in the MFC field. In this review, materials, electrochemistry, system development and scale-up systems of MFCs studied so far are reviewed, and future prospects and directions of MFC technology are presented.